GPR180 is a new member of the Golgi-dynamics domain seven-transmembrane helix protein family - Sarah-Ana Mitrovic; Chamalee Demalgiriya-Gamage; Lisa-Maria Winter; Tobias Kiechle; Rebecca Ebenhoch; Heike Neubauer; Birgit Stierstorfer; Lee Frego; Christian Wolfrum; Sophia Reindl; Herbert Nar (Communications Biology)
Abstract GOLD domain seven-transmembrane helix (GOST) proteins form a new protein family involved in trafficking of membrane-associated cargo. They share a characteristic extracellular/luminal Golgi-dynamics (GOLD) domain, possibly responsible for ligand recognition. Based on structural homology, GPR180 is a new member of this protein family, but little is known about the cellular role of GPR180. Here we show the X-ray structure of the N-terminal domain of GPR180 (1.9 Å) and can confirm the homology to GOLD domains. Using cellular imaging we show the localization of GPR180 in intracellular vesicular structures implying its exposure to acidic pH environments. With Hydrogen/Deuterium Exchange-Mass Spectrometry (HDX-MS) we identify pH-dependent conformational changes, which can be mapped to a putative ligand binding site in the transmembrane region. The results reveal GPR180’s role in intracellular vesicles and offer insights into the pH-dependent function of this conserved GOST protein.